Community-based tourism issues in Pujon Kidul Tourism Village, Pujon Sub-district, Malang Regency - Nirwikara Widhiwidhana Prasetyanto; Lucyana Trimo; Iwan Setiawan (Universitas Merdeka Malang, 2023)
Tourism sector nowadays is one of sector that contributed to Indonesian economy. One of effort to ensure that people can get economic benefit from tourism sector are development of tourism villages. Tourism village can be defined as forms of accommodation, attractions and supporting facilities that are integrated with the life, traditions and local wisdom of rural communities. The development of rural tourism is a form of community-based tourism. Community-based tourism is a platform for local communities to gain economic benefits by offering tourism products that include local people's lives, culture and natural resources. One of village that success on managed their tourism sector is Pujon Kidul Tourism Village that located in Pujon District, Malang Regency, East Java Province. But nowadays, Pujon Kidul Tourism Village threatened decline of competitiveness caused by decline of tourist visits and lack quality of human resources. This research aim to identify problems in the development of community-based tourism in the Pujon Kidul Tourism Village along with their root causes by using fishbone analysis and Miles Huberman interactive model. The results of the research show that the main problem of tourism development in Pujon Kidul Village is the decline in competitiveness. The decline in competitiveness is caused by the post-pandemic of COVID-19 visit rate not yet recovering and the low quality of human resources.